2005
DOI: 10.1128/mcb.25.17.7592-7604.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Scaffold Kinase Suppressor of Ras 1 (KSR1) Regulates Adipogenesis

Abstract: Mitogen-activated protein kinase pathways are implicated in the regulation of cell differentiation, although their precise roles in many differentiation programs remain elusive. The Raf/MEK/extracellular signal-regulated kinase (ERK) kinase cascade has been proposed to both promote and inhibit adipogenesis. Here, we titrate expression of the molecular scaffold kinase suppressor of Ras 1 (KSR1) to regulate signaling through the Raf/MEK/ERK/p90 ribosomal S6 kinase (RSK) kinase cascade and show how it determines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
92
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 93 publications
4
92
1
Order By: Relevance
“…3 and 4) (37). However, ERK activation must be constrained within a narrow range by physiological levels of KSR1 to limit proliferative signals and promote adipogenesis (36,37). Therefore, KSR1 may be required to interact with MEK and moderate its activity when a biological effect requires restrained ERK activation (e.g., during differentiation).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 and 4) (37). However, ERK activation must be constrained within a narrow range by physiological levels of KSR1 to limit proliferative signals and promote adipogenesis (36,37). Therefore, KSR1 may be required to interact with MEK and moderate its activity when a biological effect requires restrained ERK activation (e.g., during differentiation).…”
Section: Discussionmentioning
confidence: 99%
“…Signaling through the Raf/ MEK/ERK cascade moderates cell fate decisions depending upon cellular context. Control of signal output through molecular scaffolds has been proposed as one of several nodes directing cell fate (35,36). In both primary and immortal MEFs, KSR1 expression moderates ERK activity to affect a cell fate ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KSR2 Ϫ/Ϫ mice become spontaneously obese and possess cellular defects in both glucose uptake and fatty acid oxidation (13). KSR1 Ϫ/Ϫ mice have enlarged adipocytes and in vitro defects in adipogenesis and lipid accumulation (37). Because KSR proteins regulate both metabolism and tumorigenesis, we designed a study to determine how KSR1 impacts metabolism driven by oncogenic Ras.…”
mentioning
confidence: 99%
“…In C. elegans, KSR2 is required for Ras-mediated signaling during germ line meiotic progression and functions redundantly with KSR1 during development of the excretory system, hermaphrodite vulva, and male spicules (46). Subsequent studies in mammalian systems showed that KSR1 and KSR2 interact with Raf, MEK, and ERK to coordinate the intensity and duration of ERK signaling (3,9,10,29,31,54,62,63). Manipulation of KSR1 in mouse embryo fibroblasts (MEFs) revealed the intricate regulation of ERK signaling to enhance the oncogenic potential of Ras, adipogenic differentiation, and replicative senescence (29-31).…”
mentioning
confidence: 99%